Improving The Teachers Instructional Capacity through Assistance in Creating Microlearning-Based Learning Media - Maisyaroh; Juharyanto; Amirul Adha, Maulana; Lesmana, Indra; Angelie, Hanika; Fadhila, Isadatul (Fakultas Ekonomi dan Bisnis Universitas Negeri Jakarta, 2024)
This community service activity aims to provide insight and knowledge of microlearning learning media for teachers in laboratory elementary schools. The training and mentoring approach is used in this community service activity. This community service activity is carried out through the stages of socialization, training, technology application, mentoring and evaluation, and program sustainability. At the evaluation stage, it was carried out with pre-test and post- test sheets which were then analyzed using the SPSS 24.0 program. Based on the results of post-test calculations, there was a significant improvement in the skills of participants before and after participating in training activities. Thus, it can be concluded that there is a need for regular training and mentoring activities, especially in increasing the instructional capacity of teachers in the current digital era. Through this community service activity, it is hoped that it will be able to produce a teaching module and post-activity monitoring.